Analysis Of Covid-19 Tax Incentives On Tax Revenues - et. al., Diana Sari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Covid-19 pandemic is a global problem that affects every aspect of almost all countries, especially the economic aspects. The Indonesian government states that the Covid-19 pandemic is an unnatural disaster that affects economic stability as well as state revenue, which is exacerbated by the existence of an incentive scheme.This study aims to analyze the provision of tax incentives by the government to respond to the economic impact caused by the Covid-19 pandemic, as well as the impact on tax revenue on the tax incentive scheme or policy undertaken. This research is a descriptive study with a qualitative approach, which describes an event that becomes a phenomenon, then explains the situation based on the data obtained and analyzed.From several of the incentives and tax policies undertaken, more emphasis is placed on the regulatory function than on the budgetary. This step was taken to face the difficult economic conditions due to Covid-19. Losses in the form of loss of tax revenue due to the consequences of tax incentives can be calculated through the Tax Expenditure analysis, to measure the effectiveness of the tax incentives provided.